Lesson Study For Learning Community (Lslc) In Early Childhood At Tamansari Distrct - Milah Nurkamilah; Anggia Suci Pratiwi; Asti Tri Lestari; Aep Sunendar; Mujiarto Mujiarto; Budi Hendrawan; Belgis Nurhaliza; Tami Aspi Zahda Hidayah; Mia Indah Lestari; Rani Nurhidayah; N. Wiwin Wahyuni; Nurrina Firdaus; Yani H (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Lesson study is a process of improvement the quality of learning activities that emphasize a collaborative process for a group of teachers to identify learning problems, design learning scenarios, implement and evaluate through continuous plan, do, see and reflection activities. The Teacher Working Group (Kelompok Kerja Guru (KKG)) for Early Childhood Education in Tamansari sub-district has the potential to form a learning community through lesson study, as an effort to develop early childhood teacher competency in developing materials and designing learning activities in the classroom. Mathematics, Language and Arts are very important to be introduced and mastered by children from an early age. The objectives of this community service are 1) Forming a learning community through lesson study activities at the early childhood education in Tamanasari sub-district 2) increasing teacher knowledge about lesson study activities in developing the quality of learning at early childhood institutions in Tamansari Sub-district, Tasikmalaya City, 3) Assisting lesson study activities in working groups in early childhood teacher in Tamansari District. The method used is training and mentoring lesson study. The results of community service are 1) The formation of a school-based learning community in early childhood education at Tamansari sub-district. 2) Increasing the knowledge of earli childhood teachers in carrying out lesson study activities, 3) Increasing the professional and pedagogical competence of teachers in developing mathematics, language and dance learning in early childhood education.